Empowerment of the Batik Craftsmen in Telaga Biru Village, Tanjung Bumi District, Bangkalan Regency - Zamla, Elive Zanoba; Ansori, Moh; Fitriyah, Ries Dyah (Proceedings of International Conference on Da'wa and Communication, 2023)
This research focuses on several aspects: first, the empowerment strategy of batik craftsmen in Telaga Biru Village, Tanjung Bumi Subdistrict, Bangkalan Regency; second, the outcomes and impacts that have arisen from the empowerment of the batik craftsmen community in that place; third, the relevance of empowering the batik craftsmen community with the da’wah. The research method employed by the researcher is the ABCD method. The results of this research are as follows: First, the strategy employed in empowering the batik craftsmen in that place involves forming and strengthening the batik craftsmen group's institutions, developing their skills, online marketing development, packaging model, and quality enhancement, partner and business network development, and reinforcing local government support for batik craftsmen; Second, the changes and impacts resulting from the empowerment of batik craftsmen include an increased economic status, the further development of batik-making skills, the expansion of marketing models and networks, which significantly contribute to the welfare improvement of the craftsmen; Third, empowering batik craftsmen in that community aligns with the concept of da’wah bil hal, where the objective is to enhance economic quality in pursuit of achieving happiness in this world and the hereafter.